Notes on tango in the music of Julio Viera. (Revista Argentina de Musicología, 2018)
This article deals with a piece by Argentine composer Julio Viera, Cuatro serenatas a la luna, considered from the point of view of the relationships between tango and Argentine contemporary music. The article postulates two basic statements: a) that this composition is oriented by the idea of a distant tango, or tango as a sort of point of arrival, and b) that tango is in Viera’s music more a focus or a distant force than a “real” presence, and that it is precisely because of that distance that tango becomes aesthetically meaningful.
Keywords: Julio Viera; Cuatro serenatas a la luna; tango; distance; focus